Association between weekend warrior physical activity pattern and bmi with mental health status among utar Kampar university students - Cheah, Xing Ling (2023)
Nowadays, people including university students are busy with daily workloads or academic tasks and tend to engage in physical activity only during their leisure time. Thus, the term “weekend warrior” was best described as those who participate in physical activity for two sessions in a week and meet the requirements of ≥ 150 minutes of moderate-intensity or ≥ 75 minutes of vigorous-intensity activities. Additionally, mental health status also become one of the most concerning issues among university students. Several factors, particularly physical activity and body mass index (BMI) play a vital role in shaping individuals’ mental well-being as they potentially exert significant influences on their overall emotional and psychological health. Therefore, this study aimed to investigate the association between weekend warriors and BMI with mental health status at Universiti Tunku Abdul Rahman (UTAR). A cross sectional study was conducted with around 163 respondents recruited through the convenience sampling method. The physical activity patterns and mental health status of the respondents were accessed using the validated International iii Physical Activity Questionnaire – Short Form (IPAQ-SF) and General Health Questionnaire (GHQ-12). The chi-square test was used to determine the association between variables whereas the Mann-Whitney test was used to examine the comparison. This study revealed that the prevalence of weekend warriors among UTAR students was low (7.4%) when compared to other physical activity patterns. There is no significant association between mental health status with physical activity patterns (p=0.942) and BMI (p=0.333), respectively. Lastly, there were also no significant differences in mental health status between weekend warriors and physically inactive groups (p=0.96). To conclude, weekend warriors among UTAR students were considered low. Insignificant findings could be due to confounding factors that weren’t taken into consideration in this study, which might affect the accuracy of the relationship between the variables